Technological interventions for doubling farm income: An analysis of Farmer FIRST approach - G, Letha Devi; Pal, D T; Giridhar, K; Arangasamy, A; Mech, A; Kataktalware, M A; Reddy, G B M; Ramamurthy; N, Narayanaswamy B; J, Chaithra G (Indian Farming, 2022)
The total area of 869 ha was under the FFP, directly and indirectly through livestock, poultry, procurement of farm products, outreach programmes through linkages and convergence with FFP team. Adoption of FFP led to an average 4 times increase in area under fodder crops. About 59% of farmers adopted mastitis management protocols, which led to a reduction in mastitis incidence by 56%. It was observed that there was 69% of technology adoption across interventions. The area under vegetables increased by 3 times and a 1.5 times increase in farm income was observed by changing crops. During the period, an average 61% increase in milk production was reported in the study villages and an average 88% gross income increase across different technology interventions.